ZHANG YIXING'S RESISTANCE AND SELF-PROOF THROUGH THE SONG “LIT” IN THE MUSIC VIDEO “LIT” (2020) - Nurni Wahyu Wuryandari; Minah Febriani Budianto; Alika Raissa Anindya (TELL - US JOURNAL, 2026)
Lit (or 莲 Lian or “Lotus”) is a music video created by Zhang Yixing (also known as Lay), a vocalist, songwriter, and member of EXO, a group under SM Entertainment since 2012. Eight years after his debut, Zhang released a solo album entitled “Lit”, which successfully set a new record in China, and in the same year, founded Chromosome Entertainment, his own agency based in Beijing. In 2022, Zhang terminated his contract with SM Ent. This article will reveal Zhang's efforts to resist and rise through “Lit”. Zhang's way of presenting resistance is carried out through at least three aspects, by raising a great Chinese historical figure who once lived in the past as a representation of himself, displaying the image of a lotus as a symbol of resurrection, and also creating lyrics that show resistance and proof of his existence. From the study of these aspects and also referring to the positive public response, it can be concluded that Zhang is trying to show his success as a singer who is able to gain quite a large fan base, as well as proving that he is able to rise from the difficulties during his career under SM Entertainment.